All about … settling in to school a child's perspective. Issue 10 (13th May 2019) - Barker, Beth; Tatlow-Golden, Mimi; Booth, Ailbhe; O'Farrelly, Christine
Abstract : What are children's real experiences of making the transition from early years setting to Reception? By the researchers behind the Children's Thoughts about School Study Beth Barker, Mimi Tatlow-Golden, Ailbhe Booth and Christine O'Farrelly